Dual‐activator luminescence of LuAG:Mn4+/Tb3+ phosphor for optical thermometry. Issue 12 (19th July 2019) - Xie, Chunyan; Zhao, Lu; Jiang, Bin; Mao, Jiashan; Lin, Yan; Wang, Peng; Wei, Xiantao; Yin, Min; Chen, Yonghu
Abstract: Mn 4+ and Tb 3+ singly doped and Mn 4+ /Tb 3+ codoped lutetium aluminum garnet (Lu3 Al5 O12, or simply LuAG) phosphors were synthesized and investigated for the application of optical thermometry. X‐ray powder diffraction and luminescence spectroscopy measurements were performed on all samples to analyze their crystal phases and optical properties. In particular, temperature‐dependent luminescence of the LuAG:Mn 4+ /Tb 3+ sample was measured at the temperature range of 270–420 K. The results showed that the luminescence intensity of Mn 4+ has gone through a remarkable decline while the luminescence of Tb 3+ has an only insignificant change with the rise of temperature which leads to a dramatic decrease in the fluorescence intensity ratio (FIR) between the two activator Mn 4+ and Tb 3+ . Further analysis showed that the LuAG:Mn 4+ /Tb 3+ sample used for temperature sensing has a high relative sensitivity with maximum value of 4.3% K −1 at 333 K. Our research indicated that this LuAG:Mn 4+ /Tb 3+ material is a promising candidate for FIR‐type optical temperature sensing.